Krzysztof Kieślowski’s “Camera Buff”: a revised version of “First Love” - Lubelski, Tadeusz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
The article develops its title thesis, which proposes interpreting Kieślowski’s Camera Buff (Amator, 1979), his second full-length feature film, as a revised version of his documentary First Love, made five years earlier. Both films have similar starting points ‒ the story of a couple expecting the birth of their first child. But the conclusion in each case also has something in common and results in the abandoning of a film project. The latter similarity meant that Kieślowski changed the character of the main protagonist in his full-length movie. It is no longer a documentary hero but the film auteur himself. This was probably the essence of the director’s artistic discovery made while shooting Camera Buff. It meant the abandonment of the documentary character when the prolonged relationship with him (and her) proved to be ethically dubious and his (and her) development predictable. At the same time, Kieślowski expressed his own creative experience as the film’s author creating a fictitious character in Camera Buff, inspired by various figures of real ‘prototypes’.